2022
DOI: 10.1136/heartjnl-2022-321519
|View full text |Cite
|
Sign up to set email alerts
|

Temporal association between invasive procedures and infective endocarditis

Abstract: ObjectiveAntibiotic prophylaxis has been recommended for patients at increased risk of infective endocarditis (IE) undergoing specific invasive procedures (IPs) despite a lack of data supporting its use. Therefore, antibiotic prophylaxis recommendations ceased in the mid-2000s for all but those at high IE risk undergoing invasive dental procedures. We aimed to quantify any association between IPs and IE.MethodsAll 14 731 IE hospital admissions in England between April 2010 and March 2016 were identified from n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(39 citation statements)
references
References 26 publications
1
29
0
Order By: Relevance
“…In the current issue of the journal, Thornhill et al 5 tried to identify the relationship between invasive procedures (IPs) and the occurrence of IE in the UK. Between April 2010 and March 2016, 14 731 IE hospital admissions in England were identified from national admissions data and medical records.…”
Section: What Can We Learn From the Paper From Thornhill Et Al?mentioning
confidence: 99%
See 3 more Smart Citations
“…In the current issue of the journal, Thornhill et al 5 tried to identify the relationship between invasive procedures (IPs) and the occurrence of IE in the UK. Between April 2010 and March 2016, 14 731 IE hospital admissions in England were identified from national admissions data and medical records.…”
Section: What Can We Learn From the Paper From Thornhill Et Al?mentioning
confidence: 99%
“…Regarding the procedures concerned, our feeling is that it is not yet time to scale up indications for AP in guidelines. Rather, the main principle of guidelines, which is to focus on high-risk patients, is reinforced by the observation by Thornhill et al that the link between IP and IE was mainly observed in this subgroup 5…”
Section: What Will Be the Consequences In Clinical Practice? Is It Ti...mentioning
confidence: 99%
See 2 more Smart Citations
“…All agree that excellent dental hygiene is important in prevention of IE due to oral flora but the role of pre-dental procedure oral antibiotics remains unclear. Thornhill and colleagues3 highlight an additional complexity in prevention of IE with a study showing a temporal association between invasive procedures and IE in a series of 14 731 hospital admissions for IE in England between 2010 and 2016. Using a case-crossover design in which the incidence of invasive procedures in the 3 months before the episode of IE was compared with the preceding 12 months, they observed an increased risk of IE after placement of a pacer or defibrillator, dental extractions, lower gastrointestinal endoscopy, bronchoscopy and bone marrow biopsy in patients at high IE risk (figure 2).…”
mentioning
confidence: 99%